2008
DOI: 10.1038/sj.bjc.6604806
|View full text |Cite
|
Sign up to set email alerts
|

Expression of uPAR mRNA in peripheral blood is a favourite marker for metastasis in gastric cancer cases

Abstract: Urokinase-type plasminogen activator receptor (uPAR) plays a central role in the plasminogen activation cascade and participates in extracellular matrix degradation, cell migration and invasion. We evaluated the expression level of uPAR mRNA and the presence of isolated tumour cells (ITCs) in bone marrow (BM) and peripheral blood (PB) in gastric cancer patients and clarified its clinical significance. We assessed specific uPAR mRNA expression by quantitative real-time reverse transcriptase-polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…These results suggest that sensitivity of CEA mRNA levels is higher than those of serum CEA levels. Furthermore, in a large‐scale study on 846 patients with stages I–IV gastric cancer, Kita et al 27. reported that positivity for CTC using a qRT‐PCR assay with the urokinase‐type plasminogen activator receptor was 47.8% (404/846).…”
Section: Incidence Of Ctcmentioning
confidence: 99%
“…These results suggest that sensitivity of CEA mRNA levels is higher than those of serum CEA levels. Furthermore, in a large‐scale study on 846 patients with stages I–IV gastric cancer, Kita et al 27. reported that positivity for CTC using a qRT‐PCR assay with the urokinase‐type plasminogen activator receptor was 47.8% (404/846).…”
Section: Incidence Of Ctcmentioning
confidence: 99%
“…The relation between expression of components of the PA system, especially uPAR, and clinico-pathological aspects has been explored in GC (Heiss et al, 1995b;Kawasaki et al, 1998;Zhao, Wang, Qu, Huang, & Wang, 2002;Kaneko, Konno, Baba, Tanaka, & Nakamura, 2003;Lee et al, 2004;Zhang, Zhao, Ru, & Ma, 2006;Kita et al, 2009;Alpízar-Alpízar et al, 2012;Guo, Ling, Ma, Zhou, & Zhao, 2015). One of the parameters consistently correlated with the expression of the members of this system is patient survival, which is generally shorter in patients with elevated expression, particularly of uPAR (Table 1).…”
Section: The Plasminogen Activation System and Gastric Cancermentioning
confidence: 99%
“…It is also well known that there is discordance of expression profi le between CTCs and primary tumor, and several markers for regulating metastasis and prognosis have been determined by PCR-based methods. [34][35][36][37] Furthermore, a comprehensive molecular profi ling using the cDNA microarray was performed to identify novel genes to predict gastric cancer metastasis, recurrence and prognosis, suggesting that expression of MT1-MMP in peripheral blood identifi ed by the cDNA microarray technique in gastric cancer was a powerful indicator of distant metastasis, especially for peritoneal dissemination. [38] van de Stolpe et al [39] reported that CTCs were heterogeneous and differed among different cancer types.…”
Section: Recent Development Of Molecular and Genetic Characterizationmentioning
confidence: 99%